Long‐term outcomes in patients with pulmonary embolism: results from a longitudinal cohort study. Issue 5 (27th May 2021) - Lamba, Mehul; Pickering, John W.; Than, Martin; Iles, Stephen; Beckert, Lutz
Abstract: Background: Patients with pulmonary embolism (PE) have increased mortality in short‐term; however, long‐term prognosis is not well defined. Aim: In this long‐term cohort study, we aimed to determine if PE was associated with increased risk of mortality or serious clinical events (SCE). Secondary aims were to ascertain predictors of mortality and SCE. Methods: Patients admitted with clinical suspicion of PE were prospectively recruited from July 2002 to May 2003 and followed up until March 2015. Clinical outcomes in patients with PE were compared to those without PE. SCE was defined as composite of mortality, malignancy, cardiovascular events, recurrent venous thromboembolism and chronic thromboembolic pulmonary hypertension. Results: A total of 501 patients with median follow up of 11.9 years (interquartile range 3.91–12.28) was included. PE was diagnosed in 104 (20.7%) patients. Overall, 45.9% died and 57.1% developed SCE during follow up, with no significant difference in PE and no‐PE groups (both P > 0.5). Major determinants of mortality were age (hazard ratio (HR) 1.06 per year, 95% confidence interval (CI) 1.05–1.08), malignancy (HR 2.19, 95% CI 1.64–2.91) and congestive heart failure (HR 1.72, 95% CI 1.23–2.42). Factors associated with increased risk of SCE were age (HR 1.05 per year, 95% CI 1.04–1.06), malignancy (HR 1.93, 95% CI 1.48–2.52) and congestive heart failure (HR 1.77, 95% CI 1.29–2.43). In patients without PE, elevated D‐dimer concentration was not found to be associated with diagnosis of malignancy during follow up (HR 1.31, 95% CI 0.55–3.12). Conclusions: In this prospective study, we did not find association between PE and risk of all‐cause mortality or SCE. Major determinants of poor clinical outcomes were advancing age and underlying comorbidities.